O Mercosul ante os mega-acordos regionais: O tema de desenvolvimento sustentável e meio ambiente - Marcus Maurer de Salles; Marina Amaral Egydio de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This Discussion Paper identifies the rules on environment protection provided for in the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), the Regional Comprehensive Economic Partnership (RCEP) and the African Continental Free Trade Area (AfCFTA). Furthermore, the work compares the rules provided for in these mega-agreements with the rules on environment protection available in the agreements signed by Southern Common Market (Mercosur) internally and with its external partners, as well as relating these rules to those provided for by the World Trade Organization (WTO).
Keywords: K33; F13; F15; F53; 330; mega-trade agreements; CPTPP; RCEP; environment; Mercosur; WTO